Digital Teaching Materials to Improve Students' Reading Skills Based on Ruddell Taxonomy in Senior High School - Keken Wulansari; Isah Cahyani; Andoyo Sastromiharjo (Jurnal Penelitian Pendidikan IPA, 2024)
Digital teaching materials are essential in language learning, helping students understand reading. Reading comprehension can be obtained through the process of reading comprehension. Ruddell's taxonomy classifies reading comprehension levels into three groups, namely factual, interpretative, and applicative comprehension. This study uses Ruddell's taxonomy to determine the improvement of each reading comprehension level of public high school students in Bandung City after being treated using digital modules. This research used a quantitative method with a pre-experimental one-group pretest-posttest design. The subjects in this study were 10th-grade students in three public high schools in Bandung City, namely SMAN 1 Bandung, SMAN 19 Bandung, and SMAN 20 and non-test. Data analysis techniques in this study used quantitative analysis, which consisted of descriptive statistical analysis and inferential analysis. The data were tested for normality prerequisites, then continued with the nonparametric technique of the Wilcoxon test using the SPSS 24 application. The improvement of students' reading ability was known through the Normalized Gain test. The results showed a high-category increase in interpretative comprehension, a medium-category increase in applicative comprehension, and a low-category increase in factual comprehension. The treatment, with the help of digital teaching materials, caused a rise in students' reading skills.